Measuring Leadership Behavior in Scientific Publication Trends: A Bibliometric Analysis Using Biblioshiny - Khanal, Shrimani Raj; Soneja, Sakshi (Darul Yasin Al Sys, 2025)
This study investigates trends and patterns in leadership behavior research within business contexts to clarify the field’s evolution and focal areas from 2017 to 2025. The research objective is to provide a systematic overview of publication dynamics, sources, contributing institutions and countries, and thematic structures guiding current and emerging scholarship. Methodologically, a systematic bibliometric approach was applied to peer-reviewed journal articles indexed in Scopus, with data retrieved on 16/08/2025 using a targeted query. Key findings show a general upward trajectory in publications, peaking in 2024, indicating growing scholarly interest; leading sources include Journal of Occupational and Organizational Psychology and BMJ Leader. The University of Queensland, Rijksuniversiteit Groningen, and Vrije Universiteit Amsterdam emerged as top contributing affiliations, with the UK and USA dominating country-level output. Keyword analysis highlights “leadership,” “human,” and demographic factors as central themes, while co-occurrence and thematic mapping delineate core, niche, and emerging areas spanning healthcare, gender, age, and innovation. The study concludes that leadership behavior research in business is expanding in volume and diversifying in focus. The contribution and implication are a consolidated roadmap that identifies influential outlets and actors, clarifies thematic contours, and informs future inquiry by pinpointing emergent domains and potential collaboration opportunities.